Determinants of the Acceptance of Sustainable Production Strategies among Dairy Farmers: Development and Testing of a Modified Technology Acceptance Model - Naspetti, Simona; Mandolesi, Serena; Buysse, Jeroen; Latvala, Terhi; Nicholas, Philippa; Padel, Susanne; Van Loo, Ellen J.; Zanoli, Raffaele (MDPI AG, 2017)
An extended version of the Technology Acceptance Model (TAM) was applied by means of Structural Equation Modelling to testing various hypotheses on attitudes and intentions of dairy farmers towards three novel sustainable production strategies, as well as the influence of organic practices and collaborative behaviours, such as information sharing with supply-chain partners. Data on the acceptance of three sustainable production strategies, namely ‘Agro-forestry’, ‘Alternative protein source’, and ‘Prolonged maternal feeding’ were collected by a survey of dairy farmers in six European Union (EU) countries (Austria, Belgium, Denmark, Finland, Italy, United Kingdom). We found that perceived usefulness is the key determinant of acceptance, while the intention to adopt a sustainable production strategy may derive from the influence of opinions (and behaviours) of relevant others (e.g., leading dairy farmers, family members, advisors) showing the role of interactions among farmers and other stakeholders in the adoption of innovations. Finally, the perceived usefulness of all of the investigated strategies is higher for organic farmers, while collaborative patterns reduce the impact of subjective norm on usefulness and overall acceptance. Our findings should encourage policy makers to consider the important role of supply chain management practices, including collaboration, to enhance the sustainability of dairy farming systems.
Keywords: dairy farming; technology acceptance model; structural equation modeling; dairy farms; sustainability; organic agriculture